Happiness in New Students - Novita Maulidya Jalal (Research Psychologie, Orientation et Conseil, 2024)
This research aims to determine the picture of happiness of new students. The research method used is the library research method which uses scientific articles as a source of research data. The analysis used is content analysis of the article. The results of this research show that t new students' happiness can be obtained from themselves and from their social environment. Happiness that originates from oneself, such as feelings of gratitude, health, a more optimistic outlook and a more positive attitude towards other people. Meanwhile, the source of happiness can also come from the social environment, such as the income earned, the quality of social relationships, social support and community. The impact of happiness on new students can have a positive impact including the ability to handle academic stress, as well as being more involved in campus activities.